Socialization of Student Creativity and Concentration Through Zentangle Circle Activities at SDN 1 Sindangkasih - Fardan Nurhadi; Kusuma, Dewi; Diantama, Suarifqi; Rosyid, Muhammad; Pangesti, Laora Novitasari; Aini, Muthia Qurratul (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2025)
This Community Service Activity (PKM) aims to enhance students’ creativity and understanding of visual arts through the Zentangle Circle simulation activity for sixth-grade students at SD Negeri 1 Sindangkasih. Zentangle Circle is a drawing technique that involves creating repetitive patterns within a circular composition, helping students develop concentration, patience, and aesthetic expression. The implementation method includes stages of material preparation, brief training on Zentangle drawing techniques, practical simulation, and reflective discussions to assess students’ understanding and attitudes toward art. The results showed that students were highly enthusiastic during the learning process and successfully produced artworks featuring unique pattern variations and harmonious visual compositions. Moreover, the activity improved students’ creative thinking skills, attention to detail, and time management during the art-making process. Thus, the Zentangle Circle simulation activity proved effective in fostering art appreciation and developing students’ creative potential at the elementary school level.